Removal of fluoride and hydrated silica from underground water by electrocoagulation in a flow channel reactor. (April 2020) - Castañeda, Locksley F.; Coreño, Oscar; Nava, José L.; Carreño, Gilberto
Abstract: This paper concerns simultaneous removal of fluoride and hydrated silica from groundwater (4.08 mg L −1 fluoride, 90 mg L −1 hydrated silica, 50 mg L −1 sulfate, 0.23 mg L −1 phosphate, pH 7.38 and 450 μS cm −1 conductivity) by electrocoagulation (EC), using an up-flow EC reactor, with a six-cell stack in a serpentine array, opened at the top of the cell to favor gas release. Aluminum plates were used as sacrificial electrodes. The effect of current density (4 ≤  j  ≤ 7 mA cm −2 ) and mean linear flow rate (1.2 ≤  u  ≤ 4.8 cm s −1 ), applied to the EC reactor, on the elimination of fluoride and hydrated silica was analyzed. The removal of fluoride followed the WHO guideline (<1.5 mg L −1 ), while the hydrated silica was abated at 7 mA cm −2 and 1.2 cm s −1, with energy consumption of 2.48 kWh m −3 and an overall operational cost of 0.441 USD m −3 . Spectroscopic analyses of the flocs by XRD, XRF-EDS, SEM-EDS, and FTIR indicated that hydrated silica reacted with the coagulant forming aluminosilicates, and fluoride replaced a hydroxide from aluminum aggregates, while sulfates and phosphates were removed by adsorption process onto the flocs. The well-engineered EC reactor allowed the simultaneous removal of fluoride and hydrated silica. Highlights: Abatement of fluoride and silica from underground water by electrocoagulation. Flow channel cell with aluminum electrodes open to the atmosphere to favor H2 exit. Significant aluminum dosages were produced at current densities >6 mA cm −2 . Hydrated silica reacted with the coagulant forming aluminosilicates as flocs. The removal of fluoride followed the WHO recommendation, while silica was abated.